2000
DOI: 10.1093/bja/85.2.281
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein binding on the placental transfer of propofol in the human dually perfused cotyledon in vitro

Abstract: The placental transfer of propofol was investigated using the in vitro dually perfused cotyledon model of the human placenta, and the effects of protein binding in the foetal perfusate were examined. Both maternal and foetal circulations were perfused in a single-pass mode and > 30 min of stabilization was allowed before adding propofol and antipyrine to the maternal perfusate. The placental clearances of propofol were significantly increased by the augmented albumin concentrations in the foetal perfusate (1.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…According to Aungst et al who carried out permeability studies of HIV protease inhibitors and other lipophilic drugs, an enhancement in permeability was observed only for the most lipophilic (log P > 3) and highly protein-bound ( > 95%) drugs, such as chlorpromazine, nelfinavir, and DMP 851 [20]. The data in this study is in agreement with literature as the permeability of fenretinide (log P = 8.03; highly protein bound) was enhanced in the presence of BSA, whereas the permeability of antipyrine (log P = 0.39; poor plasma protein binding) [21,22] remained unchanged. However, even at a BSA concentration of 4%, fenretinide exhibited poor permeability (8.8 × 10 −8 cm/sec), which might be due to poor partitioning of the highly lipophilic moiety between the cell membrane and the receiving medium.…”
Section: Permeability Of Fenretinide In the Presence Of Plasma Proteinssupporting
confidence: 89%
“…According to Aungst et al who carried out permeability studies of HIV protease inhibitors and other lipophilic drugs, an enhancement in permeability was observed only for the most lipophilic (log P > 3) and highly protein-bound ( > 95%) drugs, such as chlorpromazine, nelfinavir, and DMP 851 [20]. The data in this study is in agreement with literature as the permeability of fenretinide (log P = 8.03; highly protein bound) was enhanced in the presence of BSA, whereas the permeability of antipyrine (log P = 0.39; poor plasma protein binding) [21,22] remained unchanged. However, even at a BSA concentration of 4%, fenretinide exhibited poor permeability (8.8 × 10 −8 cm/sec), which might be due to poor partitioning of the highly lipophilic moiety between the cell membrane and the receiving medium.…”
Section: Permeability Of Fenretinide In the Presence Of Plasma Proteinssupporting
confidence: 89%
“…The use of albumin in the perfusion medium is crucial for the oncotic pressure and microvascular permeability of the placenta 38,39 and for the placental transfer of drugs. Schenker et al 34 and He et al 40 showed with olanzapine and propofol, respectively, the significant effect of protein binding on the degree of transfer. Both of these drugs are extensively bound to plasma proteins, especially to albumin.…”
Section: Discussionmentioning
confidence: 99%
“…Schenker et al 34 and He et al 40 showed with olanzapine and propofol, respectively, the significant effect of protein binding on the degree of transfer. Both of these drugs are extensively bound to plasma proteins, especially to albumin.…”
Section: Discussionmentioning
confidence: 99%